Analysis of Competitiveness and Product Export Determinants in the East Java Manufacturing Industry - Ilham Hardina Atmaja; Dina Oktavia; M. Farandi Angesti (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2023)
This study aims to determine the export competitiveness of East Java manufactured products based on the harmonized system (HS) through Revealed Comparative Trade Advantage (RTA) analysis to cluster superior manufacturing products in the districts/cities with the largest share of the manufacturing industry using Location Quotient (LQ), as well as analyzing the determinants of East Java exports based on the destination country of trading partners in the short and long term using the Vector Error Correction Model (VECM). The results show that the RTA value of East Java is still competitive in terms of exports of manufactured commodities. In addition, the LQ analysis also concludes that there are industrial agglomerations, namely industries that are close to each other and form industrial areas, such as in Surabaya-Gresik-Sidoarjo-Malang. On the other hand, the short-term and long-term modeling shows that the GDP per capita of partner countries plays a crucial role in the sustainability of East Java’s exports. This result lead to several policy recommendations, such as preventing the demand shock from partner trading country especially non-ASEAN countries, either price and exchange rate volatility or political events as well as strengthening strategy to focus commodity production for export-oriented products.